Full‐Color Micro‐LED Display with CsPbBr3 Perovskite and CdSe Quantum Dots as Color Conversion Layers. Issue 8 (4th June 2020) - Yin, Yongming; Hu, Zhiping; Ali, Muhammad Umair; Duan, Miao; Gao, Lu; Liu, Ming; Peng, Wenxiang; Geng, Jing; Pan, Su; Wu, Yongwei; Hou, Jun; Fan, Jack; et al.
Abstract: Combining blue micro‐light‐emitting diodes (LEDs) with color conversion layers (CCLs) is a promising approach to develop efficient full‐color displays. However, no such practical display is reported so far potentially because of two major challenges, i.e., rarely available color conversion materials and severe crosstalk effect among adjacent pixels due to the thick sapphire substrates of LED chips. Here, a full‐color micro‐LED display prototype by combining rationally designed blue micro‐LEDs backlight with CsPbBr3 perovskite and CdSe QDs as green and red CCLs, respectively, is presented. The color gamut of the fabricated display can reach as high as 129% of the National Television Standards Committee (NTSC). Notably, the color gamut can still reach 126% NTSC even when only green light is converted through perovskite CCL while the other two colors are achieved from conventional micro‐LEDs. This is the first demonstration on employing perovskite materials as CCL in full‐color micro‐LEDs display. Abstract : A full‐color display prototype is demonstrated that comprises of blue micro‐light‐emitting diode (LED) backlight with CsPbBr3 perovskite and CdSe quantum dots as color conversion layers. For this, a bottom‐emitting blue micro‐LED backlight is rationally designed and successfully manufactured to avoid the crosstalk among adjacent pixels. The color gamut of the fabricated display can reach 129% of the National Television Standards Committee (NTSC).